MAP OF BRAZILIAN BIOFUELS PRODUCERS PELLETS - Garcia, D. P.; Caraschi, J. C.; Dal Bem, E. A.; Ferreira, J. P.; Souza, F. M. L.; Vieira, F. H. A.; Dias, R. R. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Pellets are biofuels that can be produced from agroforestry waste such as sugarcane bagasse, sawdust or wood shavings. Global demand for these products grows exponentially because they are low-carbon energy resources and are used by countries that need to reduce their greenhouse gas emissions to meet the agreements reached at COP21. To explore the opportunities of this promising business, it is necessary to provide information to the market regarding the production, quantity of producing industries and which lignocellulosic materials are being compacted in pellet format. To do this, this article wants to draw up an online map of Brazilian pellet producers, to find out what kind of plant biomass is used as raw material and to determine how much the country produced from this biofuel in 2017. A research with producers was carried out, with application of a Google Forms online form, which obtained a 100% response rate. Based on these data a Map of Brazilian Pellet Producers was constructed. The results revealed 18 active industries, distributed in five states, that produced 470 thousand tons of the product in 2017, made from pine, black acacia, sugar cane bagasse and coffee husks.